The Narration and its Techniques in the Play (Yawm Min Zamanina) (A Day from our Time) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Saadalla Wannous is considered from the most important seekers for new technical forms in the Arabic Theatre. This appears through his plays that bear a collection of modern technical constituents. His early plays had technical structures that gave them technical and intellectual dimensions. The plays of the nineties were qualified with new tincture in both the structure and the meaning. From the technical constituents that formed this phase in writing the scripts is the narration technique that Wannous entered as a major structure in his drama, one of which is (Yawm Min Zamanina)(A Day from our Time) , in which he used diverse narrative techniquesto contributed in the production of the indicatives and signs and achieved a dramatic integration in the Play building up.